Introduction to Go programming. (O'Reilly Media, Inc., 2014)
Get going with the Go programming language! This fast-paced video course takes you from your first Go program all the way to writing highly concurrent programs. Go is known for its simple syntax, rich library, easy concurrency, and scalability. In this course, host John Graham-Cumming teaches you the complete language, and shows you how to use Go's two special features: goroutines for concurrency and interfaces for composition. Brimming with example programs that solve real-world problems, this video covers Go through worked examples that explain language features such as channels. You'll also learn about Go's standard packages for building web applications, accessing web APIs, manipulating strings, handling dates and times, and linking Go to existing C programs. Learn about variables, simple types, and declarations Understand Go's control structures, including if and switch statements Create Go functions, and learn how multiple arguments and return values are handled Learn built-in types, including maps (associative arrays) and its powerful slice type Use goroutines and channels for easy concurrency Dive into Go's other great power: interfaces (its approach to object orientation) Learn about Go's tool chain and its built-in support for unit testing John Graham-Cumming is a wandering programmer who's lived in the UK, California, New York, and France. Along the way he's worked for a succession of technology start-ups, written the award-winning open source POPFile email program, and churned out articles for publications such as The Guardian, Dr Dobbs, and Linux Magazine.